(untitled) (Philological Studies, 2019)
In this paper an attempt is made to determine the initial meaning of the IndoEuropean root *ĝhel-(*ĝhlō-), to which such words as Latin helvus «yellowish», Greek ÷ëùñüò «light green», Russian зеленый «green» ascend. Some scientists suppose this root to mean «to shine, to sparkle», the others – «yellow», «gall», «dark blue», «gray». Words, which are derived from *ĝhel-, *ĝhlō-, *ghel-, *g’hol- etc, mean almost all colours of a rain bow: red, yellow, green, light-blue, and also white and gray. However more often meanings of this root fluctuate between colours of a central part of a spectrum. A human eye perceives these colours as more light, therefore the roots with meaning «light» must have been used for designation of these colours at an early stage of language development. One of such roots was *ĝhel-, *ĝhlō- etc. Examples of semantic evolution «light» > «yellow, green, lightblue» are Greek ãëáõêüò «light-blue», «light green», «shining, light»; Hebrew yrq and its correspondences in other Semitic languages, which mean «grow green», «be pale», «grow pale», «leaf», «ash-colour», «dusky-white», «silver coin», «gold». In all these cases one of the meanings of considered words is «white» or «light» – the relic of the initial meaning of a root.